Microstructure of complex lithium lubricants - Bodachivska, Larysa Yu.; Venger, Iryna O.; Verba, Artem Yu. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2025)
This work presents the results of studies of the microstructure and properties of lubricant samples based on synthesized complex lithium soaps of hydroxylated fatty acids from of waste food oil as a lubricant thickener. The results of scanning electron microscopy confirmed the differences in the peculiarities of the formation of the structural framework of lubricants depending on their composition, thickener concentration, complexing agents, and heat treatment temperature. It was determined that it is the lubricant thickener that binds the dispersion medium through intermolecular interaction, forms a three-dimensional interwoven microstructure, and gives the lubricant improved rheological and volumetric-mechanical properties. Complex lithium soap is more structured than simple lithium soap, although both are formed by a connected three-dimensional mesh microstructure. It has been shown that the rheological and operational properties of lubricant can be improved by using various complexing agents. The lithium complex lubricant samples are characterized by the maximum thickening effect and have lower effective viscosity values at minus 30 °C. With an increase in the concentration of the thickener, the effective viscosity of lithium complex lubricants increased, but the indicators of mechanical stability and drop point remained almost unchanged. It was found that the optimum heat treatment temperature for complex lithium lubricant is 220 °C. If the heat treatment temperature of the lubricant was exceeded, for example, at 240 °C, the microstructure of the complex lithium soap was destroyed, which led to a deterioration in viscosity and colloidal stability. The established rheological, volume-mechanical, and temperature regularities of the structure formation of the dispersed phase of lubricants can be used to select rational modes of obtaining complex lithium lubricant compositions intended for use in friction units of modern machines and mechanisms.